Effectiveness of Technology Integration in Teaching Kindergarten Learners - Golla, Ma. Veronica (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the effectiveness of technology integration in teaching Kindergarten learners at Talaga Elementary School, Morong, Rizal during School Year 2025–2026. The study utilized a descriptive research method with an experimental two-group design involving 54 Kindergarten learners selected from heterogeneous sections to ensure fair representation. Respondents were described in terms of sex, sibling position, number of children in the family, parents’ educational attainment, parents’ occupation, and monthly family income. A researcher-made parallel pretest and posttest were administered to measure learners’ performance before and after exposure to technology-integrated instruction.Findings revealed that most respondents were male, either youngest or second-born children, with parents who were mostly high school graduates. Fathers were commonly employed in the private sector, while mothers were often working in government institutions, and most families had a monthly income of ₱31,000 and above. The level of performance of both exposed and unexposed groups was generally described as Very Satisfactory. Results showed a significant difference between pretest and posttest scores, indicating improvement in performance after exposure to technology integration. However, no significant difference was found between the exposed and unexposed groups in posttest results. Furthermore, no significant differences were observed in learners’ performance when grouped according to sex, number of children in the family, parents’ educational attainment, occupation, and family income, except for sibling position, which showed a significant difference.The study concluded that technology integration contributes to learners’ academic improvement as shown in the significant pretest and posttest results. However, its effect on posttest performance between groups was not statistically significant, suggesting comparable outcomes regardless of exposure. It also concluded that learners’ demographic profile generally does not influence performance, except for sibling position.It is recommended that school heads enhance digital learning resources and facilities, while teachers are encouraged to attend training and seminars on technology integration in early childhood education. The implementation of the proposed action plan is also recommended, and further studies using other variables are encouraged.